SARAIKI HUSSAINI PROSE TRADITION : RESEARCH ANALYSIS - Mureed Hussain Arif; Dr. Sayyed Safdar Hussain (Zaban-o-Adab, 2022)
The origin of the Saraiki Hussaini Prose is a query yet to be explored. The available sources indicate that this tradition was first introduced by Ghulam Sikander Ghulam (1802-1902 AD), which is still going through its development. Few other important names with others include: Molvi Feroz, Sayed gamon shah Wasif, Nazar Hussain turk, Ghulam Hassan Shah Taib, Ghulam haider Fida, Gul Muhammad Aashiq Multani, Sayed Imam Ali Shah Shafiq, Mahmood Molai, Bakhash Fidvi, Agha Sharf Hussain, Noor Muhammad Gadai, Fida Hussain Mashkoor, Nazar Hussain Irshad Abbasi, and Sayed jafar Zaman Naqvi. The style varies from simple to rhythmical prose. It is also worth noting that few writers have incorporated the segments of poems in their proses.The tradition of saraiki Hussaini Prose has played an important role in the development and maturity of Saraiki literature at large. The scope of this article is to take a glance at the origin and development of Saraiki Hussaini Prose, using historical research methodology, ending with a descriptive conclusion.